PERAN ORANG TUA DALAM MEMINIMALISIR KENAKALAN REMAJA DI KAMPUNG KESADARAN CIKARET KOTA BOGOR - Syahra Chandra Kirana; Andriani, Luh Ade Yuanita; Yal Robiansyah; Rizal, Muhammad (Jurnal Cendekia Ihya, 2025)
The phenomenon of juvenile delinquency is increasingly widespread these days. News related to juvenile delinquency is currently in the mass media. This phenomenon also occurs in Cikaret Awareness Village, Bogor City. The delinquency that occurs in the village is classified as special juvenile delinquency such as drinking alcohol, getting pregnant outside of marriage, and online gambling. The purpose of this study is to determine the condition of juvenile delinquency in Cikaret Awareness Village, Bogor City. Furthermore, to determine the role of parents in minimizing juvenile delinquency in Cikaret Awareness Village, Bogor City and to find out the supporting factors and inhibiting factors of parents in minimizing juvenile delinquency in Cikaret Awareness Village, Bogor City. This research uses a descriptive qualitative approach with a field study research design. The data collection method consists of observation, interviews, documentation. The instruments of this research are researchers, interviews, and documentation. Data analysis was carried out in three stages, namely data reduction, data presentation, and conclusion drawing. The data validity test used source triangulation and technique triangulation. The results of this study indicate that the role of parents in minimizing juvenile delinquency in Cikaret Awareness Village, Bogor City is first, parents teach religious knowledge and manners, set a good example, invite adolescents to pray five times, recite the Koran, attend studies and advise adolescents how to get along with friends or the opposite sex according to Islamic teachings. Second, parents encourage and invite children to do positive activities. Third, parents supervise and limit the use of gadgets.